Recent developments in ion beam-induced nanostructures on AIII-BV compound semiconductors. (5th July 2018) - Trynkiewicz, E; Jany, B R; Janas, A; Krok, F
Abstract: Ion-beam sputtering of two-component substrates constitutes an alternative route for the nanofabrication of 3D (three-dimensional) structures, such as quantum dots or nanowires with unique properties like a high degree of local ordering. To allow for feasibility in precision manufacturing, control and optimization it is necessary to completely understand all the phenomena behind the evolution of nanostructures. The formation and development during the ion irradiation of similar features has been extensively studied for almost a half of century, but only over the last few years have new results appeared, ones stimulating real progress within this field. In this paper we report on the growth of such 3D nanostructures after low energy ion-beam sputtering on specific materials belonging to the group of AIII-BV binary compound crystals. Special emphasis is given to the role of sample temperature (during irradiation or post-annealing) on the evolution of nanostructure patterns and their ordering. The formation of such systems will be explained as seen from a phenomenological perspective.